ANALYSIS OF ABS THERMAL AND RHEOLOGICAL BEHAVIOR AFTER EXTRUSION - Quimas Quelho, Paulo Estevao; Alvarenga, Rafael de Aquino; Meireles, Pamela Nunes; Palmeira, Alexandre Alvarenga; Montoro, Sergio Roberto; Bandeira, Cirlene Fourquet [UNESP] (Univ Vale Paraiba-univap, 2020)
Currently, various materials are extruded, among them ABS (Acrylonitrile Butadiene Styrene) which is a thermoplastic with great applicability in various industrial sectors, especially the automotive. However, the process heating steps, as well as exposure time, may cause polymer degradation. These defects can create a number of inconveniences, ranging from piece loss to the risk of accidents due to fault propagation points. As a result, analyses are needed to prove the variation of the characteristics of the material as a function of temperature, especially if the equipment used for the extrusion process is experimental. The analyses that present low cost, speed, and which determine the temperature of degradation or the size reduction of the molecule by breaking it are based on the temperatures of degradation es, are performed via TGA (Thermogravimetric Analysis) and flow rate. Thus, the present work developed a study of the behavior of 3 different types of ABS (acrylonitrile butadiene styrene) called AE800 and AG1000 MG94, when extruded at 60RPM, to evaluate the thermo-kinetic behavior by TGA and flow rate tests. The results demonstrate that in some cases, the flow rate tests are more effective than thermogravimetry to determine this parameter and that despite the slight variations in ABS properties, its use is possible.
Keywords: Thermogravimetry; flow rate; experimental extruder